2005
DOI: 10.1557/jmr.2005.0254
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and Piezoelectric Properties of Niobium-modified BiInO3–PbTiO3 Perovskite Ceramics with High Curie Temperatures

Abstract: Piezoelectric ceramics with TC > 500 °C were projected in the perovskite BiInO3–PbTiO3 (BIPT) system based on their low tolerance factor (∼0.884). However, a stable perovskite phase could be synthesized only when the PbTiO3 (PT) content was greater than 75%. Furthermore, the large tetragonality (c/a > 1.08) and low electrical resistivity made the ceramics difficult to pole. Niobium-modified BIPT ceramics with PT contents of 80% and 85% were found to possess significantly lower dielectric loss at elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 14 publications
0
43
0
Order By: Relevance
“…[1][2][3] The operating temperature of piezoelectric ceramics is generally limited to one-half of the Curie point ͑T C ͒ due to loss of polarization, typically at temperatures lower than 200°C ͓e.g., 150°C for the conventional piezoelectric materials based on the Pb͑Zr 1−x Ti x ͒O 3 ͑PZT͔͒ with a Curie temperature, T C = 386°C. 4 After excellent piezoelectric properties for ͑1 − x͒BiScO 3 -xPbTiO 3 ͑BS-PT͒ near the morphotropic phase boundary ͑MPB͒ ͑x = 0.64͒ were reported ͑piezoelectric coefficient, d 33 = 460 pC/ N, planar coupling coefficient, k p = 0.56, and T C = 450°C͒ recently, 5,6 the discovery of several promising high temperature piezoelectric materials with high performance followed in the general BiMeO 3 -PbTiO 3 system, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] where Me can be a single cation of valency +3 ͑e.g., Sc 3+ and Fe 3+ ͒ or a mixture of cations with an average valence of +3 ͑e.g., Mg 1/2 Ti 1/2 and Ni 2/3 Nb 1/3 ͒. It has been proposed that the Bi substitution plays an unusual role of considerable enhancement of both Curie temperature ͑T C ͒ and tetragonality ͑c / a͒, which results from a strong coupling between Pb/Bi cations and B-site cations of strong ferroelectric activity, such as Ti, Zn, and Fe.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] The operating temperature of piezoelectric ceramics is generally limited to one-half of the Curie point ͑T C ͒ due to loss of polarization, typically at temperatures lower than 200°C ͓e.g., 150°C for the conventional piezoelectric materials based on the Pb͑Zr 1−x Ti x ͒O 3 ͑PZT͔͒ with a Curie temperature, T C = 386°C. 4 After excellent piezoelectric properties for ͑1 − x͒BiScO 3 -xPbTiO 3 ͑BS-PT͒ near the morphotropic phase boundary ͑MPB͒ ͑x = 0.64͒ were reported ͑piezoelectric coefficient, d 33 = 460 pC/ N, planar coupling coefficient, k p = 0.56, and T C = 450°C͒ recently, 5,6 the discovery of several promising high temperature piezoelectric materials with high performance followed in the general BiMeO 3 -PbTiO 3 system, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] where Me can be a single cation of valency +3 ͑e.g., Sc 3+ and Fe 3+ ͒ or a mixture of cations with an average valence of +3 ͑e.g., Mg 1/2 Ti 1/2 and Ni 2/3 Nb 1/3 ͒. It has been proposed that the Bi substitution plays an unusual role of considerable enhancement of both Curie temperature ͑T C ͒ and tetragonality ͑c / a͒, which results from a strong coupling between Pb/Bi cations and B-site cations of strong ferroelectric activity, such as Ti, Zn, and Fe.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, most recent studies have been focusing on nonscandium perovskites. [12][13][14][15][16][17][18][19][20][21][22][23][24] In fact, possible new compositions in BiMeO 3 -PbTiO 3 -based systems are plenty, because B-site Me of BiMeO 3 could be any combination, which gives an average valence of +3. According to the currently available literature, however, the design of BiMeO 3 -PbTiO 3 piezoelectrics faces a significant challenge in that only few systems form a MPB with PbTiO 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PNRs exist over nanometer-length scales in random directions, as a result the average lattice appears different to the local structure, ergo, the spatial coherence length is not significant enough to observe these features using CuK 1 laboratory x-rays. have resulted in sustained or enhanced tetragonality [29][30][31][32]. This behavior is a manifestation of the strong coupling between Pb/Bi and ferroelectrically active displacive B-site cations such as Ti and Fe.…”
Section: Methodsmentioning
confidence: 99%
“…13 It was expected that the Bi(Me)O 3 -PbTiO 3 compositions with higher T c > 300 C will shed light on the potentiality of achieving high temperature stability. [21][22][23][24][25][26] However, except BiScO 3 -PbTiO 3 (BS-PT), 21 the piezoelectric coefficients of the reported Bi(Me)O 3 -PbTiO 3 based ceramics, such as BiFeO 3 -PbTiO 3 (BF-PT), 22 BiInO 3 -PbTiO 3 (BI-PT), 23 Bi(Ni 1/2 Ti 1/2 )O 3 -PbTiO 3 (BNT-PT), 24 Bi(Mg 1/2 Ti 1/2 )O 3 -PbTiO 3 (BMT-PT), 25,26 etc., were lower than 300 pC/N at their respective MPBs. Furthermore, it was reported that piezoelectric coefficients exhibited different degree of degradation in binary and ternary systems, not necessarily associated with their T c /T rt , though higher T c indicating broader usage temperature range.…”
mentioning
confidence: 99%